2015
DOI: 10.1038/srep18578
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic regimen based on population analysis of residing persister cells eradicates Staphylococcus epidermidis biofilms

Abstract: Biofilm formation is a major pathogenicity strategy ofBacteria employ a variety of strategies to escape killing by antibiotics, including mutation, phenotypic variation, and change to a biofilm growth mode 1-3 . One form of phenotypic variation, known as persistence, is characterised by the presence of a subset of antibiotic-tolerant cells within a bacterial population. Persister cells pre-exist in most bacterial populations, including cultures at mid-log phase, stationary phase, and in biofilms [4][5][6] . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…In addition to the physical factors associated with biofilms, the physiological state of bacteria in biofilms contributes to antibiotic tolerance (12). Thus, apart from the issues of the permeability barrier of a biofilm matrix, the presence of a high percentage of a persister cell population has been thought to be the reason behind the tolerance of biofilms to antibiotics (11,18 cells result from the fact that it can inhibit growing and nongrowing cells equally well, and biofilm matrix probably does not act as a permeability barrier against P128. Given the variability of biofilm matrix compositions in CoNS (43,44), it is likely that the strains used in this study will form biofilms with matrices containing carbohydrates, DNA, and proteins in various proportions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the physical factors associated with biofilms, the physiological state of bacteria in biofilms contributes to antibiotic tolerance (12). Thus, apart from the issues of the permeability barrier of a biofilm matrix, the presence of a high percentage of a persister cell population has been thought to be the reason behind the tolerance of biofilms to antibiotics (11,18 cells result from the fact that it can inhibit growing and nongrowing cells equally well, and biofilm matrix probably does not act as a permeability barrier against P128. Given the variability of biofilm matrix compositions in CoNS (43,44), it is likely that the strains used in this study will form biofilms with matrices containing carbohydrates, DNA, and proteins in various proportions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that ATP depletion and expression of stationary-phase markers lead the bacterial cell into a physiological state in which it becomes tolerant to the action of antibiotics (14). It has been demonstrated that biofilms formed by S. epidermidis, S. haemolyticus, and S. lugdunensis in vitro are tolerant to the action of high concentrations of most of the antibiotics (15)(16)(17)(18). Obviously, to control CoNS infections, there is a need to develop new therapeutics, especially those with good antibiofilm activity and the ability to kill persister cells.…”
mentioning
confidence: 99%
“…Antibiotic concentrations and exposure time used in this study were 80 times the MIC for 16-17 h to minimize the survival of spontaneous antibiotic-resistant mutants and ensure eradication of tolerant but killable cells (Yang et al, 2015). The antibiotic concentrations used in this study were as follows: oxacillin, 30 µg ml…”
Section: Methodsmentioning
confidence: 99%
“…At least three TA modules exist in S. aureus including mazEF, axe1-txe1 and axe2-txe2 (Donegan & Cheung, 2009;Yoshizumi et al, 2009). Donegan et al (2010) examined the proteolytic regulation of TA systems by ClpPC in S. aureus and found that ClpP is essential for the degradation of all known S. aureus antitoxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation